Assessing and Stabilizing Aberrant Neuroplasticity in Autism Spectrum Disorder: The Potential Role of Transcranial Magnetic Stimulation - Desarkar, Pushpal; Rajji, Tarek K.; Ameis, Stephanie H.; Daskalakis, Zafiris Jeff (Frontiers in Psychiatry, 2015)
Exciting developments have taken place in the neuroscience research in Autism Spectrum Disorder (ASD) and results from these studies indicate that brain in ASD is associated with aberrant neuroplasticity. Transcranial Magnetic Stimulation (TMS) has rapidly evolved to become a widely used, safe and non-invasive neuroscientific tool to investigate a variety of neurophysiological processes, including neuroplasticity. The diagnostic and therapeutic potential of TMS in ASD is beginning to be realized. In this paper, we briefly reviewed evidence of aberrant neuroplasticity in ASD, suggested future direction in assessing neuroplasticity utilizing rTMS and discussed the potential of rTMS in rectifying aberrant neuroplasticity in ASD.